Synergistic Effect of Doripenem and Cefotaxime to Inhibit CTX-M-15 Type β-Lactamases: Biophysical and Microbiological Views - Maryam, Lubna; Khan, Asad U. (Frontiers in Pharmacology, 2017)
CTX-M-15 type β-lactamase has the ability to hydrolyse cefotaxime, a third generation cephalosporin. The infections caused by multidrug resistant strains, especially CTX-M-15 producing strains are being treated with carbapenem group of β-lactam antibiotics. The objective of the study was to know if cefotaxime in combination with doripenem, (carbapemen antibiotic) at very low concentration, inhibits the CTX-M-15 producing bacterial strains. blaCTX-M-15 gene was cloned to express CTX-M-15 enzyme and construct CTX-M-15 producing strain. The clone carrying CTX-M-15 was found susceptible to doripenem. Doripenem and CTX-M-15 binding was an endothermic and spontaneous process leading to change in polarity in the micro-environment and conformational changes of enzyme as shown by fluorescence, UV and CD spectroscopic study. The catalytic efficiency of CTX-M-15 enzyme was reduced to about 15.86% when it was treated with doripenem along with cefotaxime (in 5 times molar ratio each of doripenem and cefotaxime w.r.t CTX-M-15), as compared to the studies where enzyme’s efficiency was increased by 33% when treated with cefotaxime alone. Hence, doripenem in combination with cefotaxime reduces enzyme’s efficiency to hydrolyse cefotaxime by about 48%. FIC study showed that doripenem paired with cefotaxime showed synergistic effect against CTX-M-15 producing bacterial strain. The study concludes that doripenem at very low concentration (25 nM), induces such a structural changes in CTX-M-15 which reduced enzyme’s activity to hydrolyse cefotaxime. Hence, the synergistic use of doripenem and cefotaxime plays a significant role in inhibiting the efficiency of CTX-M-15 type β-lactamase, and may provide an alternative approach to reduce the resistance against the cephalosporin type antibiotics.